2006
DOI: 10.1074/jbc.m603517200
|View full text |Cite
|
Sign up to set email alerts
|

γ2-Adaptin, a Novel Ubiquitin-interacting Adaptor, and Nedd4 Ubiquitin Ligase Control Hepatitis B Virus Maturation

Abstract: Hepatitis B virus (HBV) budding from infected cells is a tightly regulated process that requires both core and envelope structures. Here we report that HBV uses cellular ␥2-adaptin and Nedd4, possibly in conjunction with ubiquitin, to coordinate its assembly and release. In search of interaction partners of the viral L envelope protein, we previously discovered ␥2-adaptin, a putative endosomal sorting and trafficking adaptor of the adaptor protein complex family. We now demonstrate that the viral core interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
158
1
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(170 citation statements)
references
References 50 publications
8
158
1
3
Order By: Relevance
“…The p9 YPDL domain that binds AIP1 also binds the clathrinassociated AP2 adaptor complex that sorts cargo proteins into coated pits for endocytosis, and this interaction is important for EIAV budding (55). Interestingly, HBV envelope proteins S and L were recently reported to interact with, respectively, AP2 (10) and ␥2-adaptin, a protein related to the large subunits of vesicle adaptor complexes such as AP2 (9,56). Although the possible function of S-AP2 interaction is not known, L-␥2-adaptin interaction appears important for HBV virion production (56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The p9 YPDL domain that binds AIP1 also binds the clathrinassociated AP2 adaptor complex that sorts cargo proteins into coated pits for endocytosis, and this interaction is important for EIAV budding (55). Interestingly, HBV envelope proteins S and L were recently reported to interact with, respectively, AP2 (10) and ␥2-adaptin, a protein related to the large subunits of vesicle adaptor complexes such as AP2 (9,56). Although the possible function of S-AP2 interaction is not known, L-␥2-adaptin interaction appears important for HBV virion production (56).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, HBV envelope proteins S and L were recently reported to interact with, respectively, AP2 (10) and ␥2-adaptin, a protein related to the large subunits of vesicle adaptor complexes such as AP2 (9,56). Although the possible function of S-AP2 interaction is not known, L-␥2-adaptin interaction appears important for HBV virion production (56). Thus, like EIAV, HBV budding may use host functions not only in late endocytic/MVB pathways but also in early endocytic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support and extend the data of a recent work which showed that human HBV budding involves an endosomal compartment. 18 Why do some viruses bud into endosome-like vesicles? The endosomal system clearly plays a significant role in the assembly of many retroviruses, 24 preformed HIV particles from late endosomes are infectious.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some chaperones and ␥2-adaptin were identified as host factors participating in HBV progeny formation. [16][17][18] Viruses exploit a broad arsenal of strategies to assemble and bud within cells. For example, Pox-like, Irido-like, and Asfar-like viruses induce the formation of "aggresomes," which serve as scaffolds to concentrate structural components.…”
mentioning
confidence: 99%
“…The siRNA were purchased from Dharmacon (Lafayette, CO) as nucleotide duplexes with 3′dTdT overhangs, designed to target human γ1 (5′-GGAAGAGCCUAUUCAGGUA-3′), γ2 (5′-AAACCCUGCUUUGC-UGUUAA-3′) (Rost et al, 2006) and μ1A (5′-GGCAUCAAGUAUCGG-AAGA-3′) (Janvier and Bonifacino, 2005). An alternative siRNA targeting γ2 (γ2 siRNA#2; 5′-CACAGAACACAGCAUAUCU-3′), with a 3′dTdT overhang, was purchased from Bioneer Inc (Alameda, CA).…”
Section: Yeast Three-hybrid Analysesmentioning
confidence: 99%